Proceedings of the International Symposium on Quality and Process Control in the Reduction and Casting of Alumninum and Other Light Metals, Winnipeg, Canada, August 23-26, 1987 - Macmillan, D. W. (Proceedings of the Metallurgical Society of the Canadian Institute of Mining and Metallurgy, 1987)
Covers all aspects of quality control, testing, monitoring and control of the reduction and casting processes in the light metals industry. Strong emphasis is placed on the statistical process control in the smelting and casting of aluminium, and other important practical applications.